Dampak Pembangunan Infrastruktur Di kawasan Pesisir Pantai Berdasarkan Persepsi Masyarakat di Desa Bajo Bahari - Sakinah; Efendi, Ahmad; Asrasal, Aswad (Jurnal Indragiri Penelitian Multidisiplin, 2025)
Infrastructure development is very important for the region, so the government continues to strive to develop infrastructure to improve connectivity between regions and strive to achieve equity by prioritizing development in villages. The purpose of this study is to determine the impact of infrastructure development on the economy, socio-cultural conditions, and the environment in the coastal area of Bajo Bahari Village. This study uses a qualitative descriptive research method which describes or clearly describes the impact of infrastructure development in coastal areas by measuring data calculated using a percentage descriptive technique. Data collection uses observation, questionnaire and interview methods which are then analyzed using qualitative descriptions. The results of the study show that the impact of infrastructure development on the economy of the community in Bajo Bahari Village is to reduce the cost of transportation and distribution of goods, increase access to education and the quality of learning for the local community, and increase economic accessibility and connectivity. The impact of infrastructure development on the socio-culture in Bajo Bahari Village, namely the reduction in the use of traditional vehicles, has a positive impact on inter-community relations in Bajo Bahari Village and there is a strengthening of the cultural identity of the local community. The impact of infrastructure development on the environment is an increase in household waste in Bajo Bahari village, an increase in air pollution in Bajo Bahari Village, and a negative impact on the sustainability of the ecosystem on the coast of Bajo Bahari Village.